The Perceptions of Pendidikan Guru Penggerak Towards Blended Learning - Istiqomah, Istiqomah (Jurnal Ilmiah Peuradeun, 2022)
This study aimed to report Pendidikan Guru Penggerak’s views on applying blended learning in these activities. In the study, the explanatory sequential mixed method was used as the study design. The quantitative data from the survey was conducted, followed by the follow-up interview, documentation study, and focus group discussion (FGD) as the qualitative data. To collect the data in this study, a specifically perceives of using blended learning in PGP was distributed to the total sample of 28 Guru Penggerak Angkatan 1 from Kabupaten Lombok Timur, Kabupaten Bima, and Kota Malang. Then, the interview was conducted with three selected participants from each city/regency, while the FGD involved the entire sample. The aim was to gain a deeper understanding of the research results. The results showed that participants perceived blended learning in PGP very well in terms of learning management system (LMS), synchronous and asynchronous online learning, and face-to-face mentoring and lokakarya. The realization of a learning community among fellow participants was an added value for PGP. As a result, participants could also improve their teaching skills which ICT-based.